2014
DOI: 10.4310/ajm.2014.v18.n5.a2
|View full text |Cite
|
Sign up to set email alerts
|

Dirac Lie groups

Abstract: A classical theorem of Drinfel'd states that the category of simply connected Poisson Lie groups H is isomorphic to the category of Manin triples (d, g, h), where h is the Lie algebra of H. In this paper, we consider Dirac Lie groups, that is, Lie groups H endowed with a multiplicative Courant algebroid A and a Dirac structure E ⊆ A for which the multiplication is a Dirac morphism. It turns out that the simply connected Dirac Lie groups are classified by so-called Dirac Manin triples. We give an explicit const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…11]) is a VB-subgroupoid whenever it has constant rank, see e.g. [4,19]. The analogous result for ∆ 1 follows since Id − K is also a multiplicative projection and ∆ 1 is its kernel.…”
Section: Principal Connectionsmentioning
confidence: 89%
“…11]) is a VB-subgroupoid whenever it has constant rank, see e.g. [4,19]. The analogous result for ∆ 1 follows since Id − K is also a multiplicative projection and ∆ 1 is its kernel.…”
Section: Principal Connectionsmentioning
confidence: 89%
“…When only h ⊆ d is Lagrangian then the pseudo-connection ∇ is still trivial, and W ⊆ T φ * η G coincides with the Dirac Lie group structure described in [35,36] corresponding to the Dirac Manin triple (d, h; g) ⟨·,·⟩ .…”
Section: Composition Of Courant Relations With Pseudo-dirac Structuresmentioning
confidence: 95%
“…Dirac Lie groups for which multiplication is a morphism of Manin pairs were classified in [36,35] (see also [45,29] for a different setting). There it was shown that the underlying Courant algebroid can be canonically trivialized as an action Courant algebroid A = d × H (see Example 2.8), and the Dirac structure is a constant subbundle E = g × H under this trivialization.…”
Section: Examplesmentioning
confidence: 99%
“…A VB-groupoid is a groupoid in the category of vector bundles. A CA-groupoid [46,30] is a VB-groupoid A ⇒ A over some Lie groupoid M ⇒ M such that A possesses a Courant algebroid structure (A, , ) which is multiplicative: the graph of the multiplication of A ⇒ A is a Dirac structure inside A × A × A with support on the graph of the multiplication of M. A multiplicative Manin pair (A, E) is a CA-groupoid A ⇒ A and a VB-subgroupoid E ⊂ A such that it is a Dirac structure and E is an LA-groupoid with the restricted Courant bracket. A morphism of multiplicative Manin pairs is a Manin pair morphism given by a Courant relation with support on the graph of a Lie groupoid morphism which is also a VB-subgroupoid inside the product of the CA-groupoids.…”
Section: Multiplicative Manin Pairs and Poisson Groupoidsmentioning
confidence: 99%